THE MOSLEM YOUTH POLITICAL ETHICS IN THE NOW ERA - Mahmuda Mahmuda; Reynold Padagas (Alfuad: Jurnal Sosial Keagamaan, 2022)
Ethics is a view that is considered very urgent in the order of social life. The implementation of ethics is usually carried out in accordance with the habits of people or each individual in absorbing everything, whether seen, felt or also experienced. Habits that arise are also based on various backgrounds such as appropriate norms from the customs of certain ethnic groups, religions or races. Islam has provided space and opportunity for anyone in politics, of course, in ways that are in accordance with the Shari'a based on the Koran and As-Sunnah, and cannot be separated from anyone who wants to build this country in the future. The important role of Islamic youth is certainly highly expected in changing the concept of politics, which must be accompanied by productive youths in how to take a stand and take part in politics in our loving country. In today's era, there are many problems that occur in the field regarding the character and events that originate from the youth, who are preoccupied with virtual world activities and activities that are not related to the influence of the nation, even being concerned with bad behavior among the community. Here the author wants to examine the extent to which youth are involved in playing an active role and participating in nation building which is related to knowledge in the world of politics.